(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Psychobiography is recently a fascinating field which combines both psychology and biography. This study is usually applied by the researchers to trace the psychological motives behind a historically significant individual. In this thesis considering Apostle Paul, not only as a religious man but in the perspective of historically significant personality who had played a major role in the foundation of early Christian churches brings new backdrops and also helps us in reconstructing many hidden truths